Slogan as Marketing Strategies Used in Makassar Cafes: A Semantic Analysis (KARIWARI SMART : Journal of Education Based on Local Wisdom, 2022)
This research is conducted to investigate the use of language expressions which were prescribed in the form of slogans which receives less attention in some previous studies. This research employed descriptive qualitative method. This research used field study and contextual theory from J.R Firth (1957). In collecting data, researchers conducted interview sessions between cafe owners and visitors. Results of data analysis show that the meaning of the slogan in each cafe varies based on the concept and situation, but at least among the 20 slogans, there are some slogan that has the same intention. There are 6 slogans lead more to the introduction of their place, 7 slogans lead to the situation that they provide, 2 slogans are more directed in motivating visitors to remain comfortable in the cafe. The function of the slogan that they posted also different from one to another, such as making the cafe more unique and as an identity. The linkage between the slogan and the marketing strategy can also be proven by the existence of interconnected opinions between the slogan’s user and visitors. The presence of contextual theory is also expected to be able to expand the horizons of people who do not only understand lexical language but also contextually.